Zinc Oxide as a Filler in a Hot-Mix Asphalt: Impact on Mechanical Properties - Hugo Alexander Rondón-Quintana; Karem Tatiana Forero-Rubiano; Yohan Sebastián Valderrama-Agudelo; Juan Gabriel Bastidas-Martínez; Carlos Alfonso Zafra-Mejía (Infrastructures)
Zinc oxide (ZnO) exhibits promising thermochemical properties when used as an asphalt binder modifier. Its micrometric size further enhances its potential as a substitute for natural fillers (NFs) in hot-mix asphalt (HMA). This study evaluates the effect of partially and fully replacing NFs with ZnO on the mechanical performance of HMA, addressing a research gap since the influence of ZnO as a filler in asphalt mixtures has not been previously investigated. NFs were replaced by ZnO at weight-based proportions of ZnO/NF = 25, 50, 75, and 100%. Initially, the morphology of NF and ZnO particles was analyzed using Scanning Electron Microscopy (SEM). Asphalt mastics were then produced with the same ZnO/NF proportions and subjected to conventional characterization tests, including penetration, softening point, and viscosity. In the next phase, HMA samples were designed using the Marshall method, incorporating ZnO at 0, 25, 50, and 100% replacement levels (designated as Control, HMA-25, HMA-50, and HMA-100, respectively). The mechanical performance of these mixtures was assessed through indirect tensile strength (ITS) and Cantabro tests. Based on the initial results, further evaluations were conducted on the Control, HMA-50, and HMA-100 mixtures to determine their resilient modulus, fatigue behavior under stress-controlled conditions, and resistance to permanent deformation (static creep test). The findings indicate that ZnO can replace NF in HMA without compromising Marshall stability or Cantabro strength. Additionally, ZnO-modified HMAs exhibit increases in stiffness under cyclic loading, and improvements in resistance to permanent deformation, fatigue performance, and moisture damage. These enhancements occur despite a 0.5% reduction in binder content compared to the Control HMA and a slight increase in porosity.